2018
DOI: 10.1200/jgo.18.00134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Intensive, Ultrasound-Guided Fine-Needle Aspiration Biopsy Training Workshop in Tanzania

Abstract: Background Fine-needle aspiration biopsy (FNAB) is a minimally invasive, cost-effective diagnostic tool that can be used in low-resource settings. However, adequacy and accuracy of FNAB is highly dependent on the skills of the operator and requires specialized training. Poor technique can preclude definitive diagnoses because of insufficient quality or quantity of FNAB samples. We evaluated the efficacy of an intensive training experience in Tanzania on improving ultrasound-guided FNAB techniques. Methods A 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“… 21 Our group has also previously demonstrated that intensive workshops can be effective in developing skills essential for high-quality FNAB. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 21 Our group has also previously demonstrated that intensive workshops can be effective in developing skills essential for high-quality FNAB. 24 …”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Studies have shown that various training models in cytopathology are effective, including fellowships, Webbased modules, and intensive workshops at our institution. 29,[33][34][35] However, the lack of systematic evaluation and standardization of the dozens of available cell block preparation methods limits the expansion of the use of the same in low-resource settings. [36][37][38][39] Strengthening the capacity of diagnostic cytopathology services by coupling them with ancillary tests such as cell blocks and IHC would also improve cancer care in Tanzania by shortening time and reducing the cost needed to achieve a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies applying ultrasound have shown its utility for diagnosis and interventions in the neonatal setting for neurosurgical and cardiovascular surgical disease in LMICs 22,24,34–39 . Further novel applications of ultrasound in LMIC countries have been outlined in identifying and treating orthopedic, urology, thoracic surgery and surgical oncology pathophysiologies 40–50 …”
Section: Discussionmentioning
confidence: 99%
“…22,24,[34][35][36][37][38][39] Further novel applications of ultrasound in LMIC countries have been outlined in identifying and treating orthopedic, urology, thoracic surgery and surgical oncology pathophysiologies. [40][41][42][43][44][45][46][47][48][49][50] Limitations One limitation of the study was the overall level of evidence of studies included in the cohort, which was low. Case reports and retrospective reports predominated, and randomised control trials were the least common type of study performed during the study period.…”
Section: Discussionmentioning
confidence: 99%